Evolutionary Relationship Between Platycerus Stag Beetles and Their Mycangium-Associated Yeast Symbionts - Kubota, Kôhei; Watanabe, Kana; Zhu, Xue-Jiao; Kawakami, Kako; Tanahashi, Masahiko; Fukatsu, Takema (Frontiers in Microbiology, 2020)
Adult females of stag beetles (Coleoptera: Lucanidae) possess an ovipositor-associated mycangium for conveying symbiotic microorganisms. In most lucanid species, their mycangium contains yeast symbionts of the genus Scheffersomyces Kurtzman & M. Suzuki, 2010 that are known for their xylose-fermenting capability. The lucanid genus Platycerus Geoffroy, 1762 is a group of small blue stag beetles, in which ten Japanese species constitute a monophyletic clade. Here we examined the evolutionary relationships of these Japanese Platycerus species and their yeast symbionts, together with a Korean Platycerus species and other lucanid species as outgroup taxa. Based on the internal transcribed spacer (ITS) and the intergenic spacer (IGS) sequences, the yeast symbionts of all Platycerus species were closely related to each other and formed a monophyletic clade. There is no variation in ITS sequences of the yeast symbionts of the Japanese Platycerus species. Based on IGS sequences, the yeast symbionts formed clusters that largely reflected the geographic distribution of the host insects, being shared by sympatric Platycerus species except for P. delicatulus Lewis, 1883 and P. viridicuprus Kubota, Kubota & Otobe, 2008. The symbiont phylogeny was globally not congruent with the host COI-based phylogeny, although some local congruences were observed. Statistically significant correlations were detected between the genetic distances of COI sequences of the host insects and those of IGS sequences of the yeast symbionts in Japan. These results suggest that, at least to some extent, the host insects and the yeast symbionts may have experienced co-evolutionary associations. While the Japanese Platycerus species formed a monophyletic clade in the COI phylogeny, the yeast symbionts of Japanese P. viridicuprus were very closely related to those of Korean P. hongwonpyoi Imura & Choe, 1989, suggesting the possibility that a recent secondary contact of the two beetle species during a marine withdrawal, e.g., in the last glacial period, might have resulted in an inter-specific horizontal transmission of the yeast symbiont.